Early to late Ediacaran conglomeratic wedges from a complete foreland basin cycle in the southwest São Francisco Craton, Bambuí Group, Brazil - Uhlein, G.; Uhlein, A.; Stevenson, R.; Halverson, Galen; Caxito, F.; Cox, Grant (Elsevier BV, 2017)
© 2017 Elsevier B.V. Stratigraphic, isotopic, and geochronological data from two late Neoproterozoic-aged conglomerate wedges in the southwest São Francisco craton support the interpretation that the Ediacaran Bambuí Group in east-central Brazil was deposited in a foreland basin. The Samburá Formation forms the base of the Bambuí Group in the southwestern part of the Bambuí basin and was deposited synchronously with the Brasília orogeny. It is interpreted to be a sedimentary product of a retrogradational coastal alluvial fan system deposited in an underfilled flexural foredeep during the early stages of foreland basin development sometime between 630 and 560 Ma. The basal Sete Lagoas Formation carbonates were deposited towards the cratonic margin on the forebulge, which provided an ideal environment for carbonate production. The lateral relationship between the Samburá and Sete Lagoas formations further implies that an unconformity was generated by foreland flexure, and that this unconformity separates an early Ediacaran phase of the foreland basin from a late Ediacaran phase. The Lagoa Formosa Formation was deposited in the latter phase, after peak orogenesis, with a provenance that includes post-orogenic granites and zircons as young as 560 Ma. It records a prograding turbidite fan system in the Lagoa Formosa Formation that was deposited during orogenic unroofing and basin-wide shallowing in a filled stage of the foreland basin. A shift from highly enriched d 13 C values towards global-like carbon isotopes values in carbonates within the Lagoa Formation, in conjunction with the occurrence of banded iron formation, may suggest deposition in a basin with anoxic and ferruginous deep waters in the Bambuí basin in the latest Ediacaran.